(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Hysteroscopy is the gold standard in identifying endometrial and uterine cavity pathologies. With the advancement of technology and the creation of a mini-hysteroscopes, this operation can be easily performed in the doctor's office. Complications of this operation are often related to the difficulties of entering the hysteroscope, which can lead to damage to the cervix, the creation of a false canal, bleeding, uterine perforation or difficulty in entering the hysteroscope. Considering the systemic side effects of prostaglandins, researchers are looking for less complicated drugs. Therefore, the aim of this study is to compare the effect of injectable hyoscine with vaginal misoprostol in preparing the cervix before hysteroscopy.Materials and Methods: This double-blind clinical trial was conducted on patients who underwent hysteroscopy at Mahdieh Hospital in Tehran, Iran. Patients were randomly divided into two groups and received vaginal misoprostol or injectable hyoscine 2-3 hours before surgery. Then, variables such as the ease of entering the hysteroscope, the need for Bougie for cervical dilatation, and hysteroscopy complications (damage to the cervix or uterus, pain, and bleeding), as well as the side effects of drugs were investigated and statistically analyzed.Results: According to the analysis, two groups are similar in terms of confounding variables. The results of hysteroscopy complications and drug complications showed that the use of injectable hyoscine, such as vaginal misoprostol, not only reduces complications of hysteroscopy, but also has fewer drug complications. In the current study, the overall prevalence of complications of hyoscine and misoprostol were 24% and 32%, respectively.Conclusion: Hyoscine can be a suitable drug for preparing the cervix before performing dilatation and curettage, it will also cause the cervix to dilate more easily. Using vaginal hyoscine before surgical hysteroscopy reduces the need for cervical dilatation and facilitates surgical hysteroscopy.